Force transmission between thoracic and cervical segments of the spine during prone-lying high-velocity low-amplitude spinal manipulation: A proof of principle for the concept of regional interdependence. (October 2019) - Engell, Shawn; Triano, John J.; Howarth, Samuel J.
Abstract: Background: Regional interdependence is conceptually based on observations that applying manual therapy to a remote anatomical region has an effect in the area of the patient's primary complaint. The current model for regional interdependence depends on force transmissibility within the body. This investigation sought to determine transmissibility between forces applied to the thoracic spine during prone-lying high-velocity low-amplitude spinal manipulative therapy and the cervical spine. Methods: A chiropractic treatment table was modified to allow (or disallow) translation of the headrest in the caudal-cephalad direction when unlocked (or locked). Prone-lying high-velocity low-amplitude spinal manipulative therapy was applied to the thoracic region of 9 healthy participants with the headrest in both configurations. Head and thorax kinematics and kinetics were measured at interfaces between participant and the external environment, which included the clinician's hands. Compressive forces at the cervicothoracic junction and angular kinematics of the cervical spine were derived. Ratios between the clinician-applied forces (input) and the cervical compressive force (output) were also determined. Findings: The cervical spine extended during all high-velocity low-amplitude spinal manipulative therapy trials. Force input-to-output ratios exceeded 1 for high-velocity low-amplitude spinal manipulative therapy trials performed with the headrest in the locked configuration, which was greater than ratios for the unlocked configuration. Interpretation: Forces imparted to thoracic spine during high-velocity low-amplitude spinal manipulative therapy were transmitted to the cervical spine, which provided a precursor for the regional interdependence model for manual therapy. Friction between the participant's face and the treatment table's head rest likely amplified cervical compressive forces. Highlights: Force transmissibility is integral to the concept of regional interdependence. A novel treatment table headrest was designed to assess force transmissibility. Manual therapy forces imparted to the upper back were transmitted to the neck. Friction between patient's face and treatment table likely amplified neck compression.